Unilateral Darier’s disease – case report - Węgłowska, Jolanta; Rajkowska-Strojs, Karolina; Chrzanowska, Katarzyna (Dermatology Review/Przegląd Dermatologiczny, 2017)
Introduction . Darier’s disease (dyskeratosis follicularis, keratosis follicularis, Darier-White disease, Darier disease) is a rare genodermatosis inherited in autosomal dominant manner, caused by a mutation in the ATP2A2 gene located on chromosome 12. The gene encodes SERCA2 ATPase, an enzyme responsible for the metabolism of calcium ions in the endoplasmic reticulum. Darier’s disease is characterized by small brown hyperkeratotic papules which appear already in childhood or early adolescence. Skin lesions are located primarily in seborrhoeic areas. In addition to typical skin eruptions, the clinical picture may include involvement of the nails and mucous membranes. The histopathological pattern is characterized by the coexistence of two abnormalities: acantholysis and dyskeratosis. Objective . To present and discuss a case of unilateral Darier’s disease diagnosed and treated at our medical centre. Case report . We present the case of a 46-year old woman with Darier’s disease manifesting as skin lesions in the form of typical hyperkeratotic papules localized on the left part of the trunk and on left-side limbs. The diagnosis was made on the basis of clinical features and histopathological findings. A good therapeutic effect was achieved after introducing treatment with acitretin at a dose of 25 mg/day. Conclusions . The case presented is interesting because of the rarity of unilateral Darier’s disease.